A tool for evaluating and preparing a project for obtaining external financing - A. A. Soblirov (Вестник университета)
The article deals with the issues of a comprehensive business assessment comprehensive business assessment with the help of consultants and investors for the purpose of obtaining investment. Companies often focus mainly on financial indicators when developing investment projects and searching for an investor. However, the practice of preparing projects to receive investment shows that in order to make a particular investment decision, it is necessary to apply not only the financial evaluation of the project, but also its other components. The author has conducted in-depth interviews with a group of investors and based on the results has proposed an original framework for rapid assessment of the project in the process of its preparation for investment. The framework can serve as a methodological basis for working with investors on small and medium-sized business projects, and as a tool for determining the main directions of project and business development. The framework has been tested by the author on real projects and has proved to be fit for purpose.